Short term oxygen therapy effects in hypoxemic patients measured by drawing analysis. Issue 3 (March 2015) - Fiz, José Antonio; Faundez-Zanuy, Marcos; Monte-Moreno, Enrique; Alcobé, Josep Roure; Andreo, Felipe; Gomez, Rosa; Manzano, Juan Ruiz
Highlights First paper devoted to analyze oxygen therapy effects measured by handwritten tasks. This study shows that in patients with chronic hypoxemia, a short period of oxygen therapy produces changes in psychomotor function. We show that this changes can be measured by means of drawing analysis.